Myopic Shift After Intraocular Lens Implantation in Children Less Than Two Years of Age - Ganesh, Suma; Gupta, Reena; Sethi, Sumita; Gurung, Chandra; Mehta, Raman (Nepalese Journal of Ophthalmology, 2018)
Purpose: The purpose of this study was to evaluate the myopic shift over a period of 2 years following implantation of intraocular lens (IOL) in children less than 2 years of age with axial length less than 22 mm.Method: A retrospective analysis of records of children below 2 years of age with axial length less than 22 mm who had undergone cataract surgery with primary IOL implantation over a period of 7 years was undertaken. Mean myopic shift was analyzed at 6 months, in first year, second year and end of 2 years following surgery.Results: Total 40 eyes of 23 children were included (mean age 13.55±7.38 months); with mean myopic shift at end of 2 years -2.35±2.15. Myopic shift in eyes with undercorrection in range of 3-4 D (group-I) and 5-7 D (group-II) was compared using Mann-Whitney test. Mean myopic shift at end of 2 years was -2.93±2.55 in group-I and -1.88±1.77 in group-II (p value not significant). There was no significant difference in myopic shift between two groups at 6 months and 1 year; a borderline significant difference was found in second year (p= 0.04).Conclusion: In our study amount of myopic shift in first two years in children with axial length less than 22 mm is below the expected normal. There was not much significant difference in the myopic shift over a period of 2 years in eyes, which were undercorrected by 3-4 D against those with 5-7 D. Thus aiming for less residual hyperopia by less undercorrection did not increase myopic shift. Thus high-level hyperopic glasses in the early years could be avoided and help in prevention of amblyopia after paediatric cataract surgery.